Flexible Tactile Sensing Systems: Challenges in Theoretical Research Transferring to Practical Applications - Zhiyu Yao; Wenjie Wu; Fengxian Gao; Min Gong; Liang Zhang; Dongrui Wang; Baochun Guo; Liqun Zhang; Xiang Lin (Nano-Micro Letters)
Highlights This review presents current advances in flexible tactile sensor research from multifaceted perspectives including mechanisms, materials, structural design, and system integration. It establishes performance-oriented rational design principles for sensors in practical. It summarized the challenges and strategies in translating flexible tactile sensing systems into practical applications, and proposed a research roadmap for future investigations.